Pragmatic Perspective of Item Analysis Using Microsoft Office Excel Data Analysis Tools - ETOBRO, Benjamin Akpezi; TAIWO, Olufunmi; ALAWAYE, Modupe (Ilorin Journal of Education, 2024)
This study examined with practical demonstration the validation process of item generation through item analysis to determine item difficulty level, item discrimination power and item effectiveness adopting Microsoft Office Excel Data Analysis Tools. The study employed a descriptive expo-facto survey research design. Three research questions guided the study. A 20-multiple choice question (MCQ) items in Psychological Testing in Counselling Psychology course. The MCQ was administered to 139 education students who were in their second year in Lagos State University. A sample of 40 students’ responses was extracted by systematic random sampling technique. The students’ responses were collected and item analysis carried out. Results show that levels of difficulty, discriminating power and distractor effectiveness on the MCQ items varied. Some items were easy and moderately difficult while the others were difficult to answer. It also uncovers that, in regard to discriminating power, some items are well constructed while the others were broad and ambiguously worded. Conclusively, most of the items were reliable and valid because the levels of their difficulty and discrimination power were satisfactory. Teachers and stakeholders in testing should carry out item analysis to avoid ambiguous and broad items adopting Microsoft Office Excel statistical Tools.